2018
DOI: 10.1080/15434303.2018.1477780
|View full text |Cite
|
Sign up to set email alerts
|

Fluency in Second Language Testing: Insights From Different Disciplines

Abstract: This article considers the construct of fluency in second language assessment and how it might be informed by research in applied linguistics. It briefly describes the way fluency is conceptualized in four language tests, as embodied in their respective assessment criteria, to show where the field is at present. The article then takes into account recent insights from applied linguistics, and from the fields of psycholinguistics, discourse analysis, and sociolinguistics. The article questions the current conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 94 publications
4
48
1
2
Order By: Relevance
“…The results suggest that speed and composite measures consistently distinguish fluency across proficiency levels, that length of silent pauses is a key characteristic of low‐proficiency performance (A2), and that frequency of silent pauses distinguishes the lower (A2 and B1) from higher proficiency levels. Notwithstanding the significance of such findings for fluency research and measurement, and in line with other researchers in the field (de Jong, ; Housen et al., ; Kormos, ; Skehan, , ; Tavakoli & Hunter, ), we argue that adopting a more fine‐grained approach to analyzing fluency can not only help develop a better understanding of how L2 is processed and produced, but it can also contribute toward the development of an L2 speech production model. In this regard, the current study has revealed interesting differences between the fluency construct at different proficiency levels, implying that there may be different processes at work when speakers of different proficiency levels produce L2.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results suggest that speed and composite measures consistently distinguish fluency across proficiency levels, that length of silent pauses is a key characteristic of low‐proficiency performance (A2), and that frequency of silent pauses distinguishes the lower (A2 and B1) from higher proficiency levels. Notwithstanding the significance of such findings for fluency research and measurement, and in line with other researchers in the field (de Jong, ; Housen et al., ; Kormos, ; Skehan, , ; Tavakoli & Hunter, ), we argue that adopting a more fine‐grained approach to analyzing fluency can not only help develop a better understanding of how L2 is processed and produced, but it can also contribute toward the development of an L2 speech production model. In this regard, the current study has revealed interesting differences between the fluency construct at different proficiency levels, implying that there may be different processes at work when speakers of different proficiency levels produce L2.…”
Section: Discussionsupporting
confidence: 86%
“…Fluency is one of the most common criteria featured in both holistic and analytic rating scales in many standardized tests of speaking, such as Cambridge General English tests, IELTS, TOEFL iBT (de Jong, ). Aspects of fluency featured in these rating scales include: length of speech, hesitation, repetition, self‐correction, flow of speech, pauses, speed of speech, rhythm, false starts, and evenness of speech.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Automaticity also loads with these utterance fluency elements in the analysis for the whole group. This accords well with findings by others (De Jong, 2018;Park, 2016). Recent evidence from research into acoustic/temporal aspects of fluency suggests there are threshold levels for acoustic factors such as speech rate and length or number of pauses, which need to be achieved if a speaker is to be considered fluent (Park, 2016).…”
Section: Research Question 3: Can Components Be Grouped Into Common Fsupporting
confidence: 94%
“…The term oral proficiency should not be taken synonymously to oral fluency especially in the second language assessment. De Jong (2018) and Kormo and Dénes (2004) consider fluency as one feature of oral proficiency.…”
Section: Introductionmentioning
confidence: 99%